Vocational Education in India: A Policy Analysis and Case Study of NEP 2020 Implementation - Singh, Kanwal Jeet; Gunasekaran, Vembanan (Baileo: Jurnal Sosial Humaniora, 2024)
India’s education policies, including the National Education Policy (NEP) 2020, aim to empower human resources and reduce social disparities by improving access and relevance in education. Vocational education, despite its significant potential in producing skilled labor, often remains disconnected from mainstream academic education, receiving inadequate attention and integration. As a result, graduates often lack sufficient employability and entrepreneurial skills, limiting their opportunities in the job market and in starting their own businesses. This study analyzes national education policies from 1968, 1986, 1992, up to NEP 2020, and includes a case study of the Skill Enhancement Courses at the University of Delhi. Policy analysis methods were used to evaluate policy changes, while the case study aimed to assess the practical impact of these policies. The findings show that NEP 2020 has successfully promoted the integration of vocational education with academic education, and the Skill Enhancement Courses at the University of Delhi have been effective in improving students’ employability skills. The novelty of this research lies in NEP 2020’s priority to integrate vocational education into the mainstream curriculum, demonstrated to be effective through its implementation at the University of Delhi. This study recommends strengthening the synergy between vocational and academic education to address the skills gap among graduates, particularly in the context of developing the social sciences and humanities.